Hexaaquamanganese(II) bis[4-(pyridin-2-ylmethoxy)benzoate] dihydrate - Zhang, Li-Wei; Gao, Shan; Ng, Seik Weng (International Union of Crystallography, 2011)
The MnII atom in the title salt, [Mn(H2O) 6](C13H10NO3)2·-2H 2O, lies on a center of inversion in an octa-hedron of water molecules. The cations, anions and uncoordinated water molecules are linked by O - H⋯O and O - H⋯N hydrogen bonds into a three-dimensional network. The anion is essentially planar, with an r.m.s. deviation of all non-H atoms of 0.068 Å. © Zhang et al. 2011.